Description of mother's knowledge and attitude towards providing hepatitis b immunization to babies aged 0-7 days at Kayuagung Oki City Health Center 2022 - Agustina, Dessy; Dana, Berlian; Ramadhani, Indri (Science Midwifery, 2024)
The aim of this study was to determine the description of mothers' knowledge and attitudes towards providing hepatitis B immunization to babies aged 0-7 days at the Kayuagung City Health Center. This research is researchDescriptiveusing a cross-sectional approach to determine the description of mothers' knowledge and attitudes towards providing hepatitis B immunization at the Kayuagung City Health Center in 2021. The population in this study were all mothers with babies 0-7 days old who made immunization visits in the working area of ​​the Kayuagung City Health Center in 2023. 636 babies. The research sampling technique used the Accidental Sampling Technique with the number of samples or sample size taken from the total population of babies who received hepatitis B immunization at the age of 0 - 7 days in the Kayuagung City Health Center Working Area, totaling 41 respondents. This research was carried out on January 19 – February 19 2022. The research results showed that as many as 16 respondents had poor knowledge (39.0%) and 25 respondents who had good knowledge (61.0%) and 17 respondents who had a negative attitude (41.5%) and 24 respondents who had a positive attitude (58.5%) For puskesmas in the future to continue to improve the quality of services in particularfor pregnant women and mothers who have babies aged < 7 days. And for health workers or posyandu cadres to provide information and counseling about the importance of Hepatitis B immunization.